2013
DOI: 10.5194/acpd-13-903-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of a winter regional haze event and its formation mechanism in the North China Plain

Abstract: A regional haze episode occurred in the Beijing, Tianjin and Hebei province (BTH) area in the North China Plain (NCP) from 16 to 19 January 2010. The chemical and optical properties of aerosols and the meteorological condition were investigated in this study with intensive measurement of aerosol and trace gases from 14 to 23 January 2010 at five sites. The episode was caused by the combination of anthropogenic emissions and surface air stagnation under a high pressure system followed by a low pressure system. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
3
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 35 publications
5
131
3
2
Order By: Relevance
“…Moreover, in consideration of the fact that sulfate, nitrate, ammonium and organic aerosol are the dominant components of PM 2.5 in Shanghai, gas-to-particle conversion is also likely a significant contributor to haze formation in YRD (Yao et al, 2002;Wang et al, 2006;Ye et al, 2003;Yang et al, 2005;Feng et al, 2009). Particle hygroscopic growth from high humidity and biomass burning after harvests often leads to heavy pollution in winter (Zhang et al, 2012;Zhao et al, 2013). However, most studies focus on winter, while haze in fall is also severe and complicated.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, in consideration of the fact that sulfate, nitrate, ammonium and organic aerosol are the dominant components of PM 2.5 in Shanghai, gas-to-particle conversion is also likely a significant contributor to haze formation in YRD (Yao et al, 2002;Wang et al, 2006;Ye et al, 2003;Yang et al, 2005;Feng et al, 2009). Particle hygroscopic growth from high humidity and biomass burning after harvests often leads to heavy pollution in winter (Zhang et al, 2012;Zhao et al, 2013). However, most studies focus on winter, while haze in fall is also severe and complicated.…”
Section: Introductionmentioning
confidence: 94%
“…The region suffers from serious photochemical pollution and haze (Tang et al, 2009;Han et al, 2013). The hourly average concentrations of PM 2.5 in Beijing reach 318 mg/m 3 on hazy days (Zhao et al, 2013), and cities in Hebei province suffer from even greater atmospheric pollution . Ding et al (2009) reported worsening photochemical pollution in Beijing and the North China Plain.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies on the characteristics of atmospheric aerosols during haze episodes in Beijing have been carried out during the past few years. Crustal matters, secondary aerosol, and organic materials are identified as the three main chemical components of the aerosols in Beijing Zhao et al, 2013). SO 4 2À , NO 3 À , and NH 4 þ represent the dominant water soluble inorganic ions (WSIIs) during haze episodes in aerosol (Z.Q.…”
Section: Introductionmentioning
confidence: 99%